2017
DOI: 10.1111/cns.12726
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin inhibitor ameliorates cognitive dysfunction via inhibiting nitrosative stress and NLRP3 signaling in mice with bilateral carotid artery stenosis

Abstract: These data disclose novel findings about the therapeutic potential of DY-9836, and its encapsulated nanodrug delivery system significantly enhanced the cognitive function via inhibitory effect on nitrosative stress and NLRP3 signaling in VaD mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…The macrophage content of the atherosclerotic vessel depends on the extent of the inflammatory reaction [41, 42]. Notably, several recent studies suggested that nitrosative stress is a key trigger of inflammasome activation [14, 43]. In the present study, an elevation in NLRP3 in the aortic sinus of atherosclerosis mice was observed, and a further dramatic increase was evidenced in atherosclerotic mice with GPR124 overexpression.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The macrophage content of the atherosclerotic vessel depends on the extent of the inflammatory reaction [41, 42]. Notably, several recent studies suggested that nitrosative stress is a key trigger of inflammasome activation [14, 43]. In the present study, an elevation in NLRP3 in the aortic sinus of atherosclerosis mice was observed, and a further dramatic increase was evidenced in atherosclerotic mice with GPR124 overexpression.…”
Section: Discussionsupporting
confidence: 61%
“…Accumulating evidence indicates that the molecular and cellular mechanisms associated with inflammasome signaling are potentially important during pathological disease processes [14-16]. Importantly, NLRP3 inflammasomes are required for atherogenesis and are activated by cholesterol crystals is an early event of inflammation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, immunohistochemical results confirmed that GAS decreased the expression of LC3 compared with VD rats, especially in the CA1 regions of the hippocampus (Fig. 2c-d) .Calcium/calmodulin-dependent protein kinase II (CaMKII) belonging to the CaMK familyis a serine/threonine protein kinase as an pivotal calcium signal molecule, which is the main mediator of physiologically excitatory glutamate signal [22,28,32]. CaMKII has demonstrated a critical role in autophagy regulation [29].…”
Section: Gas Reverses Suppression Of Autophagy Flux and Hyper-phosphosupporting
confidence: 53%
“…Vascular cognitive impairment (VCI) is termed as a spectrum of cognitive dysfunction associated with vascular disease origins from mild cognitive impairment to dementia . White matter damage due to chronic cerebral hypoperfusion is involved in a variety of neurological disorders including VCI . White matter hyperintensities (WMH) are the main manifestation of white matter damage, while cognitive impairment and subjective impairment are associated with severe WMH .…”
Section: Introductionmentioning
confidence: 99%